TRANSIT-ORIENTED DEVELOPMENT AND URBAN TRADE IN SEMARANG CITY - Maria Chrismastyani Pratiwi; Suzanna Ratih Sari (Journal of Information System, Applied, Management, Accounting and Research, 2026)
Urban trade development is closely related to transportation systems and regional accessibility. Semarang City, as a major trade and service center in Central Java, faces challenges such as traffic congestion, urban sprawl, and the suboptimal use of mass transportation. These conditions have contributed to increased mobility costs and reduced efficiency of economic activities. This study aims to analyze the role of Transit-Oriented Development (TOD) in supporting urban trade development in Semarang City. The research adopts a qualitative descriptive approach using policy document analysis, secondary data, and case studies of major economic activity areas. The findings indicate that TOD has the potential to enhance trade and service activities by improving accessibility, concentrating economic functions, and increasing the efficiency of consumer and labor mobility. However, weak intermodal integration and the absence of a comprehensive TOD-oriented economic plan remain significant obstacles. This study concludes that TOD can serve as an effective supporting instrument for urban trade development if consistently integrated with transportation and economic policies.